Cattle Grub Management - Phillip E. Kaufman; Emma N. I. Weeks (EDIS)
Immature warble flies, or cattle grubs, infest and harm livestock throughout the world. Warble flies also are known as “heel flies” because they cause cattle to kick at themselves, and “gad flies” because they cause cattle to “gad about” in an attempt to evade the flies. Two species of cattle grubs occur in the U.S.A., the common cattle grub, and the northern cattle grub. This 6-page fact sheet was written by P. E. Kaufman and E. N. I. Weeks and published by the UF Department of Entomology and Nematology, March 2013.